Private Equity and Local Public Finances - OLBERT, MARCEL; SEVERIN, PETER H. (Journal of Accounting Research, 2023)
ABSTRACT We study the economic impact of private equity (PE) investments on local governments, which are important corporate stakeholders. Examining over 11,000 deals and private firm data in Europe, we document that target firms' effective tax rates and total tax expenses decrease by 15% and 13% after PE deals. At the same time, target firms expand their capital expenditures and firm boundaries, but do not increase employment. Using administrative data on the public finances of German municipalities and exploiting the geographical and time‐series variation in PE deals, we document that PE activity is negatively associated with local governments' tax revenues and spending. This result is likely driven by reduced tax payments of PE portfolio firms, accompanied by only modest positive spillovers of PE investments on regional economic growth. Collectively, our findings suggest that corporate tax efficiency serves as a cost‐cutting channel in the PE sector and constrains the finances of local governments.